Designing A Busy Book With The Theme of SelfIdentity as A Learning Medium for Early Childhood Education at PAUD Ash Shidiq - Rachmawati, Ine; Solihah, Yuni Awalaturrohmah; Azahra, Fatimah; Khodijah, Tiara; Fickri Rosyid, Dzulfikar (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
The discussion about the golden age period in children has been heard by all of us very often, this very rapid development for early childhood must be balanced with the provision of training to early childhood to help in its growth and development to be maximized, the use of busy books is widely used to provide simulations and also as a teaching medium for early childhood by helping children learn in a more fun and effective way. In this research, the theme of designing a busy book with the theme of self, the sub- theme of body members for early childhood, this busy book is designed as a learning media for early childhood to introduce the names of body members, know their functions, and how to care for their body members. The method used in this research is the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). The results of this study are expected to contribute to the development of innovative and effective learning media for early childhood, teachers also use of this busy book to help children learn about their body members in a fun way.